The Dynamics of the US-Iran Relationship after the Assassination of Qassem Suleimani: Explanations and Predictions (Social Science Review, 2023)
The political dynamics of the US-Iran relationship have kept the two states always on the brink of the eruption of a major conflict. The targeted assassination of Major General Qassem Suleimani, one of the most consequential figures in Iranian military history, took the world to the brink of a global conflict on January 3, 2020. Fortunately, however, the subsequent events did not escalate to declared or undeclared war. This article provides a theoretical analysis of the conflict following the assassination of Major Suleimani to explain why and how war was avoided in this context. The analysis based on contemporary context, regional power dynamics, and relevant conditions illustrates how de-escalation of conflict was possible and argues why, in light of existing theories, there is hardly any possibility of a manifest war between the US and Iran in the near future despite prevailing in an alternate and latent form.Social Science Review, Vol. 40(1), Jun 2023 Page 185-201